Fate of heavy metals and polycyclic aromatic hydrocarbons (PAH) in sewage sludge carbonisates and ashes - A risk assessment to a thermochemical phosphorus-recycling process - Steckenmesser, Daniel (Waste management (New York, N.Y.), 2018)
Copyright © 2018 Elsevier Ltd. All rights reserved.